A bibliometric analysis of insomnia in adolescent - Gao, Tianci; Tao, Yulei; Wang, Qianfei; Liu, Jiayi; Du, Zekun; Xing, YueYi; Chen, Fenqiao; Mei, Jianqiang (Frontiers in Psychiatry, 2023)
Background: The negative effects of insomnia on adolescents' development, academic performance, and quality of life place a burden on families, schools, and society. As one of the most important research directions for insomnia, adolescent insomnia has significant research value, social value, and practical significance. Unfortunately, there is no bibliometric analysis in this field of study. This study aims to analyze published articles using bibliometrics, summarize the current research progress and hot topics in this field systematically and exhaustively, and predict the future direction and trend of research. Method: For this study, the Web of Science Core Collection (WoSCC) database was searched between 2002 and 2022 for publications related to adolescent insomnia. The R-bibliometrix, VOSViewer, and CiteSpace software were utilized for bibliometric analysis. Results: This investigation included 2468 publications from 3102 institutions in 87 countries, led by China and the United States. This field of research has entered a period of rapid development since 2017. The journal with the most publications on adolescent insomnia is Sleep, which is also the most co-cited journal. American Journal of Psychology has the highest impact factor among the top 10 journals. These papers were written by 10605 authors; notably, Liu Xianchen emerged as the author with the highest frequency of publications, while Mary A. Carskadon was the most frequently co-cited author. Mental health and comorbid diseases were the main research directions in this field. "Depression", "anxiety", "mental health", "COVID-19", "stress", "quality of life", "heart rate variability", and "attention-deficit hyperactivity disorder" were hot spots and trends in this field at the current moment.The research on adolescent insomnia has social value, research value, and research potential; its development is accelerating, and an increasing number of researchers are focusing on it. This study summarized and analyzed the development process, hot spots, and trends of adolescent insomnia research using bibliometric analysis, which identified the current hot topics in this field and predicted the development trend for the future.